RISK ANALYSIS OF LANDING SHIP TANK WARSHIPS FOR DELIVERY OF LOGISTIC ASSISTANCE IN ISLANDED EARTHQUAKE LOCATION - I Made Suwandiyana; Ahmadi Ahmadi; Priyadi Hartoko (JOURNAL ASRO, 2021)
The future threat to the world, including Indonesia, is natural disasters. The Navy as a means of state defense places natural disaster management as a form of military operation task other than war. Landing Ship Tank (LST) type warship is a defense system capable of delivering logistics on a large scale directly to disaster locations via beaching. The main problem is still finding delays and failures in logistics delivery caused by equipment damage with the biggest loss being the sinking of warships. The aim of the research is to minimize the occurrence of risk events by making a risk management design based on the ISO 31000 framework which focuses on warship operations. The method used by the House of Risk (HOR) is divided into two stages. HOR stage 1 focuses on ranking the Aggregate Risk Potential (ARP) value with the help of a Pareto diagram to determine the selected risk agent, which then requires treatment on a priority scale. The results of the HOR stage 1 are then entered into the HOR stage 2 to obtain the most effective preventive action. The results obtained, there are 8 risk agents that need to be handled. Furthermore, based on brainstorming with the Expert (the commander of the warship) obtained 12 mitigation actions that can be implemented immediately. Keywords: Risk Analysis, Landing Ship Tank, HOR